Verification of DNA motifs in Arabidopsis using CRISPR/Cas9‐mediated mutagenesis. Issue 8 (20th February 2018) - Li, Chenlong; Chen, Chen; Chen, Huhui; Wang, Suikang; Chen, Xuemei; Cui, Yuhai
Summary: Transcription factors (TFs) and chromatin‐modifying factors (CMFs) access chromatin by recognizing specific DNA motifs in their target genes. Chromatin immunoprecipitation followed by next‐generation sequencing (ChIP‐seq) has been widely used to discover the potential DNA‐binding motifs for both TFs and CMFs. Yet, an in vivo method for verifying DNA motifs captured by ChIP‐seq is lacking in plants. Here, we describe the use of clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated 9 (Cas9) to verify DNA motifs in their native genomic context in Arabidopsis. Using a single‐guide RNA (sgRNA) targeting the DNA motif bound by REF6, a DNA sequence‐specific H3K27 demethylase in plants, we generated stable transgenic plants where the motif was disrupted in a REF6 target gene. We also deleted a cluster of multiple motifs from another REF6 target gene using a pair of sgRNAs, targeting upstream and downstream regions of the cluster, respectively. We demonstrated that endogenous genes with motifs disrupted and/or deleted become inaccessible to REF6. This strategy should be widely applicable for in vivo verification of DNA motifs identified by ChIP‐seq in plants.